2016
DOI: 10.1038/mt.2016.67
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Clinical Variables in Cancer Patients Treated With Adenoviral Oncolytic Immunotherapy

Abstract: The development of oncolytic viruses has recently made great progress towards being available to cancer patients. With the breakthrough into clinics, it is crucial to analyze the existing clinical experience and use it as a basis for treatment improvements. Here, we report clinical data from 290 patients treated with oncolytic adenovirus. Using clinical variables and treatment characteristics, we constructed statistical models with regard to treatment response and overall survival (OS). Additionally, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…First we tested the antitumor efficacy of Onc.Ad5/3D24 because this oncolytic virus has been clinically tested in patients with solid tumors, including HNSCC. 23 We injected the virus locally into both FaDu and SCC-47 xenograft models and found that it had minimal anti-tumor effects ( Figure S5), suggesting that, like CAR T cells, oncolysis alone is insufficient to cure bulky HNSCCs. Next we confirmed that co-infection of Onc.Ad with HDAdIL12_PDL1 (CAd12_PDL1; Onc.Ad:HDAd = 1:10 4 ) amplified IL-12p70 and PD-L1-blocking antibody expression in co-infected FaDu and SCC-47 cells in vitro ( Figure 4B).…”
Section: Benefits Of Combining Helper-dependent and Oncads (Cad)mentioning
confidence: 99%
“…First we tested the antitumor efficacy of Onc.Ad5/3D24 because this oncolytic virus has been clinically tested in patients with solid tumors, including HNSCC. 23 We injected the virus locally into both FaDu and SCC-47 xenograft models and found that it had minimal anti-tumor effects ( Figure S5), suggesting that, like CAR T cells, oncolysis alone is insufficient to cure bulky HNSCCs. Next we confirmed that co-infection of Onc.Ad with HDAdIL12_PDL1 (CAd12_PDL1; Onc.Ad:HDAd = 1:10 4 ) amplified IL-12p70 and PD-L1-blocking antibody expression in co-infected FaDu and SCC-47 cells in vitro ( Figure 4B).…”
Section: Benefits Of Combining Helper-dependent and Oncads (Cad)mentioning
confidence: 99%
“…We have previously found that neutrophil-to-lymphocyte ratio (NLR) significantly predicts survival in patients treated with oncolytic adenovirus [ 6 ]. In order to verify that IL-8 is not merely reflecting the neutrophil/lymphocyte balance in these patients, we combined baseline IL-8 and neutrophil-to-lymphocyte ratio status in a survival analysis (Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…The association of high IL-8 and high neutrophils is logical, since neutrophil recruitment and activation is one of the main functions of IL-8 [ 44 ]. We have previously found that neutrophil-to-lymphocyte ratio predicts survival in adenovirus treated cancer patients [ 6 ]. Therefore, it was interesting that IL-8 status was able to improve its predictive ability significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations